Comparison of Static and Dynamic Postural Stability Between Individuals With and Without Forward Head Posture - Abbasi, Hamed; Alizadeh, Mohammad Hossein; Rajabi, Reza; Mohammadi, Fariba (Physical treatments, 2020)
Purpose: The growing popularity of media devices such as smartphones and computers has made humankind to acquire forward head posture increasingly. This study aimed to compare static and dynamic postural stability between people with and without forward head posture. Methods: 15 male students with normal posture (24±4 years, 173±6 cm and 70±6 kg) and 15 male students with forward head posture (25±3 years, 178±7 cm and 68±5 kg) were selected purposefully according to the Cranio-vertebral angle. Biodex Stability System was evaluated used to measure Static and dynamic postural stability.  Results: The results showed a significant difference between the two groups in dynamic postural stability in both open and closed eyes conditions(P<0.05), whereas no significant difference was observed in static postural stability in both open and closed eyes conditions (P>0.05).  Conclusion: Individuals with forward head posture performed weaker in dynamic postural stability than normal ones, as a result, forward head posture is considered as one of the factors disturbing dynamic postural stability.